2013
DOI: 10.17659/01.2013.0081
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Perforation in a Lady with Twin Gestation and Severe Preeclampsia

Abstract: We present a case where the clinical manifestation of a duodenal perforation was masked by preeclampsia during the initial workup. A 22 year G2A1, 32 weeks pregnant female presented with symptoms of impending eclampsia and blood pressure of 190/120 mm Hg. Emergency cesarean section was done for failed induction. Subsequently, she developed subacute bacterial peritonitis leading to acute renal failure and disseminated intravascular coagulation. On post-operative day 4, the abdominal wound dressing was stained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The hematological and biochemical derangements as well as clinical features culminated in a SOFA score of 6 on admission. The association between hypertensive disorders in pregnancy and gastroduodenal perforation is not clear [16]. The first case had pregnancy-induced hypertension and the second case imminent eclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hematological and biochemical derangements as well as clinical features culminated in a SOFA score of 6 on admission. The association between hypertensive disorders in pregnancy and gastroduodenal perforation is not clear [16]. The first case had pregnancy-induced hypertension and the second case imminent eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of diagnosis of imminent eclampsia, the second patient had epigastric pain. Ranganna et al reported a case of duodenal perforation in a nullip with twin gestation with imminent eclampsia in whom the clinical manifestation of the perforation was masked by that of the imminent eclampsia [16]. Perforation leads to chemical peritonitis and this can lead to shock, electrolyte imbalance, sepsis and acute kidney injury all of which may be potentially fatal [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical signs and symptom were progressive abdominal distension, abdominal pain and tenderness, tachycardia and fever. Two patients were diagnosed with preeclampsia [10,19] and one with eclampsia [20]. Signs and symptoms of peptic ulcer in these cases were primarily attributed to preeclampsia features.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneocentesis was performed in three cases [19][20][21] and was diagnostic in two [19,21], resulting in laparotomy. Peritoneocentesis may be a practical tool to rule out hemoperitoneum.…”
Section: Discussionmentioning
confidence: 99%